"Living high-training low": effect of moderate-altitude acclimatization with low-altitude training on performance - Levine, B. D.; Stray-Gundersen, J. (Journal of Applied Physiology, 1997)
The principal objective of this study was to test the hypothesis that acclimatization to moderate altitude (2,500m) plus training at low altitude (1,250m) -- "living high-training low" -- improves sea level performance in well trained runners, more than an equivalent sea level or altitude control. 39 competitive runners (27 m, 12 f) completed: a) a 2 week lead in phase, followed by b) 4 weeks of upervised training at sea level; c) 4 weeks of field training camp randomized to three groups: 1) living at moderate altitude (2,500m) and training at low altitude (1,250m) - "high -low," n=13; 2) living and training at moderate altitude (2,500m) - "high-high," n=13; or 3) living and training in a mountain environment at sea level (150m) - "low-low," n=13. A 5,000m time trial was the primary measure of performance; laboratory outcomes included: maximal O2 uptake (VO2max), anaerobic capacity (accumulated O2 deficit), maximal steady state (MSS, ventilatory threshold). running economy, velocity at VO2 max, and blood compartment volumes. Both altitude groups significantly increased VO2 max (5%) in direct proportion to an increase in red cell mass volume (9%; r = 0.37, P < 0.05), neither of which changed in the control. Five-kilometer time was improved by the field training camp only in the high-low group (13.4 +/- 10 s), in direct proportion to the increase in VO2 max (r = 0.65, P < 0.01). Velocity at VO2 max and MSS also improved only in the high-low group. Four weeks of living high-training low improves sea-level running performance in trained runners due to altitude acclimatization (increase in red cell mass volume and VO2 max) and maintenance of sea-level training velocities, most likely accounting for the increase in velocity at VO2 max and MSS.